Exploring the Challenges of Senior Midwives in Providing Mentorship to Pre-service Student Midwives at Women and Newborn Hospital, University Teaching Hospital, Lusaka, Zambia - Betty, Miyanda-Mwiinga; Catherine, Ngoma-Mubita; Marjorie, Kabinga-Makukula (British Journal of Healthcare and Medical Research, 2025)
This study aimed to explore the barriers and challenges senior midwives face when mentoring pre-service student midwives during clinical placements at the Women and Newborn Hospital within the University Teaching Hospitals in Zambia. An existential-phenomenological design was used, a qualitative research approach that seeks to understand how individuals experience, interpret, and give meaning to their lived realities within specific social and contextual worlds. Grounded in phenomenology and existential philosophy, particularly the work of Heidegger and Merleau-Ponty, this design recognises that human experience is embodied, emotional, relational, and situated, and that individuals are constantly being in the world rather than detached observers of reality. The qualitative data from the interviews and focus group discussions were analysed through a collective and iterative process. Senior midwives identified several barriers to effective mentorship, including excessive numbers of students, brief clinical placement periods, hostile attitudes among staff and toward resources, inconsistent application of supervision guidelines, insufficient time to provide feedback, and congested clinical environments. Patient care responsibilities were frequently prioritized over mentorship, limiting opportunities for guided learning. Despite these challenges, midwives employed adaptive strategies such as improvising with limited resources, encouraging students to bring their own equipment, and mentoring during less busy shifts. This study underscores the importance of addressing barriers and innovating current strategies in daily nursing midwives' routines. The key results highlight the need to create a sustainable, continuous mentoring process. Further research should focus on developing frameworks to improve mentoring for senior midwives.